Cerebral Sinovenous Thrombosis Associated With Iron Deficiency Anemia Secondary to Severe Menorrhagia: A Case Report. (September 2014) - Corrales-Medina, Fernando F.; Grant, Leon; Egas-Bejar, Daniela; Valdivia-Ascuna, Zoila; Rodriguez, Nidra; Mancias, Pedro
Cerebral sinovenous thrombosis is a rare condition presenting with a wide spectrum of nonspecific symptoms that can make early diagnosis difficult. Cerebral sinovenous thrombosis has been associated with various etiologies. Iron deficiency anemia associated with cerebral sinovenous thrombosis in teenagers is rare. We present a teenage patient with complete thrombosis of the vein of Galen, straight sinus, and left internal cerebral vein associated with iron deficiency anemia due to severe menorrhagia. Mechanisms that can explain the association between iron deficiency anemia and thrombosis are discussed.